Indonesia Sharia Stock Index and Global Sharia Stock Index - Lisa Kustina; Adrianna Syariefur Rakhmat (JURNAL ILMIAH MANAJEMEN & BISNIS, 2020)
This study aims to analyze the effect of the Global Sharia Stock Exchange on the Indonesia Sharia Stock Price Index in Indonesia Stock Exchange for the study period of 2016 to 2018. On 31 December 2015, the ASEAN Economic Community began to be implemented, then resulting in a free flow of goods, services, and investments, so this study took samples starting in 2016. Dependent variables used are the Indonesia Sharia Stock Index, while the independent variables are Dubai Financial Market General Index (DFMGI), European Dow Jones Islamic Market Index, (DJIEU), Dow Jones Islamic Market Index 25 USD (Malaysia) and Tadawull All Share Index (Saudi Arabia). While the independent variable used is the Indonesia Sharia stock index (ISSI). The data used are monthly stock index data from all sharia stock indexes in Indonesia, Malaysia, the US, Japan, Dubai, and Saudi Arabia from 2016 to 2018. This research was processed using Eviews 10. The results of this study indicate that partially Dubai Financial Market General Index (DFMGI) and the European Dow Jones Islamic Market Index (DJIEU) have no significant effect on the Indonesia Sharia stock index, while the Dow Jones Islamic Market Index 25 USD (Malaysia) and the Tadawull All Share Index (Saudi Arabia) have a significant effect on the Indonesia Sharia Stock Index.